2016
DOI: 10.1111/trf.13955
|View full text |Cite
|
Sign up to set email alerts
|

Relative efficacy of tranexamic acid and preoperative anemia treatment for reducing transfusions in total joint arthroplasty

Abstract: Having a decreased Hb was shown to be an independent risk factor both for requiring a perioperative blood transfusion and for the volume of transfusion. The very modest increase in Hb achieved by the costly and time-consuming preoperative anemia optimization program, however, may not be justified when the use of intraoperative TXA led to drastic reductions in both transfusions and transfusion volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
(54 reference statements)
0
14
0
1
Order By: Relevance
“…Numerous investigators have demonstrated that TXA reduces transfusion in TJA . The questions that persist surrounding TXA are not so much whether it works but rather in whom to use it .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigators have demonstrated that TXA reduces transfusion in TJA . The questions that persist surrounding TXA are not so much whether it works but rather in whom to use it .…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the transfusion requests related specifically to surgical procedures (an important focus of PBM projects), we chose, as a pilot, the orthopaedic specialty to verify: adequacy of the number of RBC requested for each surgery, percentage of patients submitted to surgery previously presenting with anaemia and the relation of the presurgical haemoglobin levels with the need for intra‐ and postoperative transfusion. This specialty was chosen following the trend of what was done in other PBM programmes in other continents , and considering the fact that this specialty does not generally have patients that require specific transfusion triggers or that require large volume transfusions (as in the case of cardiac surgeries), which facilitates their evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been published on the use of TXA in total joint arthroplasty, and have produced positive clinical results. A retrospective cohort study involved 872 416 patients who had total hip or knee arthroplasty in 510 US hospitals by 2006–2012, and the results demonstrated that patients receiving TXA ( vs those who did not) showed lower rates of allogeneic or autologous transfusion (7.7% vs 20.1%), while not having increased risk of thromboembolic complications (0.6% vs 0.8%).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may be explained as follows. First, although TXA may have the potential risk of triggering thrombosis, this has not been confirmed. Some authors even suggest that TXA can reduce the risk of thrombosis by reducing the need for blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation